Combinação de aditivos em dietas para bovinos de corte em confinamento - Lamag, Anderson (2019)
The objective of this work was to evaluate the effect of different combinations of additives on dry matter intake, apparent digestibility, performance and carcass yield of beef cattle in feedlot. A total of 1326 Nelore cattle were used, not castrated, with a mean age of 18 months and an initial mean body weight of 290.81 ± 40.25 kg. The diet had a voluminous ratio: concentrate of 23:77, with supply of corn silage as a bulky source. The following additions of additives were evaluated in the diet: 27 mg monensin / kg DM (Mon); 22 mg monensin + 19 mg virginiamycin / kg DM (Mon + Vm) and 22 mg monensin + 500 mg functional oil / kg DM (Mon + OFcm). Statistical analyzes were obtained using a linear model using initial weight and confinement days as covariables and comparisons between treatments using linear orthogonal contrasts with a significance level of 5%. Consumption of dry matter and nutrients expressed in kg day-1 and percentage of body weight did not differ. The final body weight and mean daily gain of animals supplemented with monensin alone did not differ from those supplemented with monensin. However, the final body weight, mean daily gain and carcass gain processing efficiency of animals supplemented with monensin combined with virginiamycin were higher than those supplemented with monensin and functional oil. Carcass yield, digestibility and feed efficiency were not influenced by the combination of additives. The association or not of monensin with the other additives provides similar performance in confined cattle. The monensin and virginiamycin combination is shown to be superior to monensin and performance oil.